Penilaian Implementasi e-Government di PUSTEKOM Kemendikbud berbasis metode PEGI - Rahayu, Puji (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
According to the Survey UN (United Nations) in 2014, e-government and innovation can provide major opportunities to transform the public administration becomes a tool of sustainable development, provide services more transparent and more accountable. Formerly, the development of government services can be done with a variety of channels, either through online services, big data, social media, mobile applications, or cloud computing, have expanded our perception of e-government services. The research aims to assess the level of achievement of e-Government implementation in the Ministry of Education and Culture of the Republic of Indonesia. Assessment is measured by the Indonesian e-Government Rating framework. The data in this research are obtained by qualitative approach and descriptive data analysis. The finding of this research that the implementation of Â e-Government in Ministry of Education and Culture in the category of "Very Good". Based on such an assessment, given the recommendation: Â assemblying policies Governance of ICT, aligning the ICT Master Plan by principle of ICT Governance, fulfilling documents related to human Resources of ICT and the application documents, the standardization of domain labeling and e-education, completing information systems/ technogy of management and organizational design, assemblying the development plan of e-education content, and development plans of information system and information technology.